Circulating tumor DNA as a non‐invasive substitute to metastasis biopsy for tumor genotyping and personalized medicine in a prospective trial across all tumor types. Issue 4 (26th December 2014) - Lebofsky, Ronald; Decraene, Charles; Bernard, Virginie; Kamal, Maud; Blin, Anthony; Leroy, Quentin; Rio Frio, Thomas; Pierron, Gaëlle; Callens, Céline; Bieche, Ivan; Saliou, Adrien; Madic, Jordan; et al.
Abstract : Cell‐free tumor DNA (ctDNA) has the potential to enable non‐invasive diagnostic tests for personalized medicine in providing similar molecular information as that derived from invasive tumor biopsies. The histology‐independent phase II SHIVA trial matches patients with targeted therapeutics based on previous screening of multiple somatic mutations using metastatic biopsies. To evaluate the utility of ctDNA in this trial, as an ancillary study we performed de novo detection of somatic mutations using plasma DNA compared to metastasis biopsies in 34 patients covering 18 different tumor types, scanning 46 genes and more than 6800 COSMIC mutations with a multiplexed next‐generation sequencing panel. In 27 patients, 28 of 29 mutations identified in metastasis biopsies (97%) were detected in matched ctDNA. Among these 27 patients, one additional mutation was found in ctDNA only. In the seven other patients, mutation detection from metastasis biopsy failed due to inadequate biopsy material, but was successful in all plasma DNA samples providing three more potential actionable mutations. These results suggest that ctDNA analysis is a potential alternative and/or replacement to analyses using costly, harmful and lengthy tissue biopsies of metastasis, irrespective of cancer type and metastatic site, for multiplexed mutation detection in selecting personalized therapies based on the patient's tumor genetic content. Highlights: We report de novo multiplexed detection of targetable ctDNA mutations. We report ctDNA mutations detection from multiple tumor types (SHIVA trial). There is no correlation between ctDNA and total plasma DNA quantity. ctDNA corresponds to ∼25% of total cfDNA fraction for detectable plasma mutations. ctDNA is as remarkable surrogate of tumor biopsy for de novo mutation calling.